Prognostic significance of subtle coronary calcification in patients with zero coronary artery calcium score: From the CONFIRM registry. (September 2020) - Han, Donghee; Klein, Eyal; Friedman, John; Gransar, Heidi; Achenbach, Stephan; Al-Mallah, Mouaz H.; Budoff, Matthew J.; Cademartiri, Filippo; Maffei, Erica; Callister, Tracy Q.; Chinnaiyan, Kavitha; Chow, Benjamin J.W.; et al.
Abstract: Background and aims: The Agatston coronary artery calcium score (CACS) may fail to identify small or less dense coronary calcification that can be detected on coronary CT angiography (CCTA). We investigated the prevalence and prognostic importance of subtle calcified plaques on CCTA among individuals with CACS 0. Methods: From the prospective multicenter CONFIRM registry, we evaluated patients without known CAD who underwent CAC scan and CCTA. CACS was categorized as 0, 1–10, 11–100, 101–400, and >400. Patients with CACS 0 were stratified according to the visual presence of coronary plaques on CCTA. Plaque composition was categorized as non-calcified (NCP), mixed (MP) and calcified (CP). The primary outcome was a major adverse cardiac event (MACE) which was defined as death and myocardial infarction. Results: Of 4049 patients, 1741 (43%) had a CACS 0. NCP and plaques that contained calcium (MP or CP) were detected by CCTA in 110 patients (6% of CACS 0) and 64 patients (4% of CACS 0), respectively. During a 5.6 years median follow-up (IQR 5.1–6.2 years), 413 MACE events occurred (13%). Patients with CACS 0 and MP/CP detected by CCTA had similar MACE risk compared to patients with CACS 1–10 ( p  = 0.868). In patients with CACS 0, after adjustment for risk factors and symptom, MP/CP was associated with an increased MACE risk compared to those with entirely normal CCTA (HR 2.39, 95% CI [1.09–5.24], p  = 0.030). Conclusions: A small but non-negligible proportion of patients with CACS 0 had identifiable coronary calcification, which was associated with increased MACE risk. Modifying CAC image acquisition and/or scoring methods could improve the detection of subtle coronary calcification. Graphical abstract: Image 1 Highlights: The Agatston coronary artery calcium score (CACS) method may fail to detect very small or less dense calcified plaques. 4% of patients with CACS 0 had evidence of coronary calcification (mixed plaque [MP] or calcified plaque [CP]) on CCTA. In patients with CACS 0, MP/CP was associated with an increased risk of MACE compared to those with no plaque by CCTA. Modification of CAC scan acquisition and/or scoring methods are needed in order to improve plaque detection sensitivity.